Environmental factors and particle size shape the community structure of airborne total and pathogenic bacteria in a university campus - Tianer Zhang; Tianer Zhang; Mengmeng Liu; Mengmeng Liu; Dalin Zhou; Zhijing Ma; Liu Chen; Danchen Wu; Haitao Diao; Wanru Wang; Die Li; Quan Zhen (Frontiers Media S.A., 2024)
Given the dense population on university campuses, indoor and outdoor airborne bacterial contamination may lead to the rapid spread of diseases in a university environment. However, there are few studies of the characteristics of airborne and pathogenic bacterial communities in different sites on a university campus. In this study, we collected particulate matter samples from indoor and outdoor locations at a university in Bengbu City, Anhui Province, China, and analyzed the community characteristics of airborne and pathogenic bacteria using a high-throughput sequencing technique. The results showed that the composition of the dominant airborne and pathogenic bacterial communities was consistent among sites at the phylum and genus levels, with differences in their relative abundance. There were significant differences in the structure of the airborne and pathogenic bacterial communities between indoor and outdoor sites (p < 0.05). An analysis of similarities (ANOSIM) indicated that the structure of airborne bacterial communities in indoor sites was influenced by the room occupancy rate, ventilation conditions, and the extent of indoor furnishing (p < 0.05), while the structure of pathogenic bacterial communities was influenced by the number of individuals and spatial dimensions (p < 0.05). The impact of particle size on the structure of airborne and pathogenic bacterial communities was relatively minor. A total of 194 suspected pathogenic bacterial species were identified, accounting for 0.0001-1.3923% of the total airborne bacteria, all of which were conditional pathogens. Among them, Saccharopolyspora rectivirgula, Acinetobacter johnsonii, and Moraxella osloensis exhibited relatively high relative abundance, accounting for 24.40, 16.22, and 8.66% of the total pathogenic bacteria, respectively. Moreover, 18 emerging or re-emerging pathogenic bacterial species with significant implications for human health were identified, although their relative abundance was relatively low (0.5098%). The relative abundance of pathogenic bacteria in indoor environments was significantly higher than outdoors, with the laboratory and dormitory having the highest levels. The findings of this study provide valuable guidance for the prevention and control of airborne bacterial contamination and the associated health risks in both a campus environment and other public spaces with high occupancy rates.